An alternative process for the synthesis of the key intermediate of ritlecitinib. (19th November 2021) - Wang, Zhongqing; Xu, Guobin; Lu, Huixiong; Wu, Shuming; Liao, Shouzhu; Hu, Yanqing; Lin, Jidi; Liu, Zijian
Abstract: An alternative synthetic route towards the key intermediate of ritlecitinib has been developed. Stereochemistry of intermediate 10 was introduced based on chiral pool strategy by employing d -pyroglutamate derivative 20 as starting material and chiral salt resolution strategy by using safer resolving agents without exothermic risk. The economical cost was lowered by avoiding noble metals catalyzed hydrogenation while maintaining a high-quality delivery of key intermediate 10 with excellent selectivity and purity. From process operability perspectives, all chromatographic purifications were eliminated and the process is readily scalable. Graphical abstract: Image 1